2015
DOI: 10.1080/19476337.2014.990519
|View full text |Cite
|
Sign up to set email alerts
|

Technological failures caused by cephalexin in set-type sheep’s milk yogurt

Abstract: Given their broad spectrum, cephalosporins are used for combating mastitis in dairy species. Many cephalosporins, such as cephalexin, have not been authorized for use in lactating sheep and because veterinary drugs for use in small species are lacking, the regulations of several countries allow extra-label use. Incorrect use of extra-label tools may cause residues in milk, and could negatively affect public health by provoking technological failures in the dairy fermenting processes. The effects of cephalexin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…If milk and its products are obtained from the clandestine market, then the hazards and risks are those mentioned above. These issues can result in low quality products, low yields, microbiological fermentation failures due to possible antibiotic residues and taste defects (Fleischer et al ., 2001; Novés et al ., 2015). These taste defects may be of microbiological origin, caused by bacteria that produce proteolytic and lipolytic enzymes, and/or physical factors such as oxidative rancidity caused by exposure to light (Cadwallader and Singh, 2009).…”
Section: Main Threats Associated With Raw Milk and Its Productsmentioning
confidence: 99%
“…If milk and its products are obtained from the clandestine market, then the hazards and risks are those mentioned above. These issues can result in low quality products, low yields, microbiological fermentation failures due to possible antibiotic residues and taste defects (Fleischer et al ., 2001; Novés et al ., 2015). These taste defects may be of microbiological origin, caused by bacteria that produce proteolytic and lipolytic enzymes, and/or physical factors such as oxidative rancidity caused by exposure to light (Cadwallader and Singh, 2009).…”
Section: Main Threats Associated With Raw Milk and Its Productsmentioning
confidence: 99%
“…The presence of such substances also affects the dairy industry as bacteria sensitive to antibiotics most widely used in many fermentation processes, result in spoiling the organoleptic properties of the final products, and coagulation or maturation of dairy products may fail. Studies into sheep milk yoghurt have observed that the levels of betalactam residues that come close to or below the MRL could delay coagulation by more than 40 minutes, cause variations in final compositions (Berruga et al, 2007a(Berruga et al, , 2008bNovés et al, 2015), and could delay the pH in pressed cheeses from lowering by between 5-300 minutes (Berruga et al, 2007b). It is noteworthy that most heat treatments employed in the dairy industry have no strong impact on residues since they do, in general, not deactivate after heat treatment (Roca et al, 2010, Zorraquino et al, 2008).…”
Section: Effect Of the Presence Of Antibiotic Residues In Milkmentioning
confidence: 99%
“…β-lactam residues in milk and other animal tissues are a cause of concern for authorities and consumers: they induce allergic reactions in hypersensitive individuals [32], interfere with the fermentation processes used by dairy industries [33] and contribute to the spreading of antimicrobial resistance [34]. To prevent such consequences, the European Union has established specific threshold values for each drug in food commodities, namely the Maximum Residues Limits (MRLs) [35].…”
Section: Introductionmentioning
confidence: 99%